Kisah Turunnya Adam Ke Bumi dalam Al-Qur’an dan Al-Kitab: Analisis Pendekatan Julia Kristeva - Prayogo, Pandu; Ishaac, Muhamad; Musthafa, Hilman; Fakhrurridha, Hujjatul; Suratin, Sonia Isna (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This article examines the narrative of the descent of Prophet Adam and Eve from heaven to earth, by comparing the perspectives contained in the Qur'an and the Bible. This article is a qualitative research that uses a linguistic approach with a focus on intertextuality analysis. The aim is to explore and compare the narrative of Adam's descent in the Qur'an and the Bible through the lens of Julia Kristeva's theory, which emphasizes the social, cultural, and historical context in understanding the text. Data were collected from literature studies, including primary sources such as the texts of the Qur'an, the Bible, and Kristeva's works. The analysis was conducted descriptively-analystically to examine the intertextual elements and dynamics of meaning from both texts. This study also applies theoretical triangulation to ensure the validity of the data by comparing the results of the analysis with other theoretical perspectives. With this approach, the article aims to reveal the deeper meaning of the story of Adam's descent and its contribution to the understanding of human identity and morality in a religious context. This article highlights differences in narrative details, such as the location of the descent and the consequences of Adam and Eve's actions, and how this story reflects gender and identity dynamics. By referring to the social and cultural context, this article shows that the story of Adam is not only a religious story, but also a reflection on the complex human condition.